Perceived supports and evidence-based teaching in college STEM - Meghan E. Bathgate; Oriana R. Aragón; Andrew J. Cavanagh; Jonathan K. Waterhouse; Jennifer Frederick; Mark J. Graham (SpringerOpen, 2019)
Abstract Background Evidence-based teaching, such as active learning, is associated with increases in student learning and engagement. Although many faculty are beginning to adopt innovative practices, traditional lecture-based teaching tends to dominate college science education. What are the factors associated with faculty's decision to incorporate evidence-based teaching? While there are known barriers that limit adoption of evidence-based practices in science classrooms (e.g., lack of time, student resistance), the present work reveals that instructors' perceptions of supports (e.g., access to teaching resources, encouragement from colleagues) shows a stronger relationship to instructors' use of evidence-based teaching. Results These results come from a uniquely large dataset of college science faculty and instructors from across the USA (n = 584), who received training in evidence-based teaching. Multiple linear regression analyses of the relationship among perceived supports, barriers, and reported implementation of evidence-based practices showed that instructors report greater implementation when they perceive more social, personal, and resource supports even when barriers are also indicated as present. Conclusion Faculty's perceived supports, not perceived barriers, are most strongly related to their reported implementation of evidence-based teaching. These findings suggest relevant stakeholders devote increased attention identifying and building the factors that promote evidence-based teaching in addition to reducing what inhibits it.